Analysis of Bumper Media Needs for Interactive Ethnographic Videos Assisted by Artificial Intelligence for Material on Recognizing Shapes and Colors in Elementary School - Fhelenia Ardana; Makmum Raharjo; Farhan Yadi (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
This study aimed to analyze the need for developing Artificial Intelligence (AI)-assisted interactive ethnographic bumper video media in elementary school Art Education, particularly for teaching shapes, colors, and local cultural motifs from the Senjang Palembang tradition. The study employed a descriptive mixed-methods approach involving 3 teachers and 315 students from three elementary schools. Data were collected through observations, interviews, and structured questionnaires covering six dimensions of needs analysis: pedagogical, technical, cognitive, aesthetic, socio-cultural, and evaluative aspects, integrated into the components of students, teachers, media, and instructional design. Quantitative data were analyzed using percentages and Spearman Rank correlation, while qualitative data supported the interpretation of findings. The results revealed that all dimensions of needs were categorized as high to very high, with cognitive and aesthetic aspects emerging as the most dominant. These findings highlight the importance of developing visually engaging, culturally contextualized media that effectively supports information processing. In addition, technical and evaluative aspects were identified as essential for ensuring accessibility and learning feedback. This study provides a conceptual foundation for developing AI-based ethnographic media that is pedagogically appropriate, culturally relevant, and aligned with the Merdeka Curriculum.